Incidence and Progress of Vesicoureteric Reflux after Primary Fulguration of Posterior Urethral Valves (Bangladesh Journal of Endosurgery, 2013)
Introduction: Posterior urethral valve (PUV) is the most frequent cause of urethral obstruction in male child. These lesions may result in lifelong disabilities with incontinence and decreased renal function despite optimal medical management. Primary fulguration without upper tract diversion is the preferred modality of treatment in most cases of PUV. Regular follow-up is needed to check completion of valve fulguration, renal function, status of hydronephrosis, vesicoureteric reflux (VUR), urinary tract infection (UTI), and bladder function.Materials and Methods: An interventional study among 30 purposively selected patients of PUV was conducted from December 2009 to July 2011. Most of the patients presented with weak urinary stream, dribbling of urine, straining at micturition, UTI, and palpable bladder. All children were subjected to ultrasonography (USG), blood urea, serum creatinine, routine urine examination, and culture studies. Structured questionnaire was used to collect information regarding improvement or disappearance of VUR and renal functional status before and after primary fulguration of PUV.Results: Ages ranged from 10 days to 14 years; 16 were between 1year and 14 years (53.3%), 11(36.7%) were infants, and the rest 03(10%) were neonates. Average serum creatinine levels were found gradually decreasing significantly (p < 0.01) in subsequent follow-ups. Average blood urea nitrogen (BUN) was also decreased significantly (p < 0.05). VUR was present in 63.3% cases. Non-VUR was found in 60% cases on right side and 50% cases on left side. On the third follow-up after 3 months it became 73.3% on right side and 63.3% on left side. Positive correlation found in Pearson correlation test about the changes of reflux grades before and after fulguration was significant (p < 0.001). It was significant on both left and right kidneys. Positive correlation found in Pearson correlation test about the changes of GFR before and after fulguration was also significant (p < 0.001). Collected data was cleaned, edited, and analyzed with the help of software SPSS window version 15.0.Conclusion: VUR disappeared in some cases and decreased in majority of the cases by 3 months after adequate restoration of urethral patency. Renal function came to normal range in two thirds of the cases.DOI: http://dx.doi.org/10.11593/bje.2013.0102.0013Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 23-28